A responsabilidade civil do médico pelo fato do serviço no Código de Defesa do Consumidor com base na informação - Caldeira, Patrícia (2008)
The present study investigates the medical activity and procedures to assess responsibility, focusing on the right/duty to inform. Information involves presentation of the product or service, as well as safety, the legitimate expectation of the consumer. Absence, insufficiency or inadequacy of information may motivate the duty to compensate. Evaluation of the doctor s responsibility is proposed, all rules pertaining to general suppliers being applicable to the doctor as well. The objective is to demonstrate the need to protect the consumer with the observance by the supplier, including the doctor, of the duty to give clear, precise and adequate information referring to the service provided, whereas violation of the duty to inform characterizes objective responsibility